Az újraszervezés gyakorlata: mozgástervezés - Györgyjakab, Enikő (Symbolon, 2025)
The Practice of Reorganization: Movement Composition Movement composition is a fundamental practice in the training system I use, focused on organizing conscious movement material. It is integrated throughout the educational process, running parallel to the teaching of movement techniques and skill development. The pedagogical aim is to develop proficiency in organizing the actor’s movement material. Through physical experience, movement composition shows that the actor’s presence can be seen as an independent layer of the theatrical performance. It fosters a deep awareness of the actor’s relationship with space, time, and movement, exploring their potential in the creative process. While the movement score created may not be a full theatrical scene, it carries the potential for one, providing participants with the experience of theatrical creation from the early stages of training. Movement composition emphasizes that the actor is a co-creator in the artistic process, not merely a performer, taking responsibility for various aspects of the creation.